A Brief Overview on Poverty in Iran: Comparison With the World - Habib-allah Shahriyari; Masoud Amiri; Zahra Shahriyari (Shahrekord University of Medical Sciences, 2018)
Poverty is a multi-dimensional problem and various researchers, based on their field, have investigated different aspects of poverty. Moreover, poverty, as a global problem, could be an interesting subject for both developed and developing countries. In recent decades, both international organizations and different countries have had some programs for reducing poverty. The evaluatinon of power and capacity of national economy for coping with poverty is the first essential step. In addition, in a longterm period, poverty would depend on economy development, but in the short-term, considering the proper concept of poverty with potential available financial resources is necessary. Then, calculation of poverty line and percentage of poor people using the appropriate methods is the next step. In recent decades, Iran's economy has had different problems such as rising inflation, unemployment, balance of payments deficit in macroeconomics and its effect on poverty and in equal income distribution in microeconomics. Effects of the price balancing on poverty is also an important subject that its evaluation is possible with the data acquired after subsides policy. Another aspect is the picture of poverty in rural and urban communities in the last year and near to implementation of this policy. This article presented an overall picture of poverty in urban and rural communities of Iran as well as worldly defined indices in poverty literature.